Digital Arabic Learning in Education and Training Center UNIDA Gontor: Case Study of Arabic Language Training at Al-Azhar IIBS Karanganyar - Arifin, Muhammad Syamsul; Sa’idah, Mandrasi Amira; Nur, Ifa Rodifah; Dzulfiqar, Ahmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to examine the efforts of the University of Darussalam Gontor Education and Training Center (Pusdiklat) in digitizing learning Arabic as a foreign language or TAFL (Teaching Arabic as a Foreign Language). The focus of this research is a digital-based Arabic language education and training program and character-building organized by the UNIDA Gontor Education and Training Center in collaboration with Al-Azhar International Islamic Boarding School (IIBS) Karanganyar, Central Java. This research uses a qualitative approach and case study method. Data were obtained through three instruments, namely: participatory observation, in-depth interviews, and documentation studies. Data from observations, interviews, and documentation were analyzed qualitatively and comprehensively using the interactive Miles and Huberman method. This study concludes that 1) the program for learning Arabic as a digital-based foreign language is carried out referring to the language competency standards of Darussalam Gontor University and the Indonesian National Qualifications Framework (KKNI) in the preparation of learning objectives, materials, methods, and evaluation; 2) digital teaching media in the form of power points for teaching materials durūsullugah, maharat al-kalām, and mufradat; and 3) the character building program is implemented through language extracurricular activities in collaboration with the Adab curriculum owned by Al-Azhar IIBS.